Clinical, Hormonal, and Ultrasound Characteristics of Patients with Newly Diagnosed Graves’ Disease And Different Thyroid Antibody Profiles - Mekova R. (Sciendo, 2019)
Objective: Graves’ disease (GD) is characterized by elevated TSH-receptor antibodies (TRAb) and less often – thyroid peroxidase (TPOAb) and thyroglobulin antibodies (TgAb). Our aim was to examine the hormonal and ultrasound characteristics of patients with newly diagnosed GD with differing positive thyroid antibodies.